2011
DOI: 10.1007/s10342-011-0551-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of silviculture on dead wood and on the distribution and frequency of tree microhabitats in montane beech-fir forests of the Pyrenees

Abstract: In forest ecosystems, the level of biodiversity is strongly linked to dead wood and tree microhabitats. To evaluate the influence of current forest management on the availability of dead wood and on the abundance and distribution of microhabitats, we studied the volume and diversity of dead wood objects and the distribution and frequency of cavities, dendrothelms, cracks, bark losses and sporophores of saproxylic fungi in montane beech-fir stands. We compared stands unmanaged for 50 or 100 years with continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 56 publications
3
59
0
Order By: Relevance
“…On the contrary, forest harvesting and most other conventional silvicultural interventions do not normally aim to produce large amounts of dead wood typically found in old-growth forest. Larrieu et al (2012) confirmed that management of montane beech-fir stands reduces the total volume of dead wood and the snag volume, modifies the pattern of decay stages and also reduces the tree species diversity and the diversity of tree microhabitats. Yet, in the framework of sustainable forest management, a better knowledge of the factor influencing the occurrence of dead wood would allow foresters to adopt scientifically-base practices to preserve biodiversity.…”
Section: Introductionsupporting
confidence: 50%
“…On the contrary, forest harvesting and most other conventional silvicultural interventions do not normally aim to produce large amounts of dead wood typically found in old-growth forest. Larrieu et al (2012) confirmed that management of montane beech-fir stands reduces the total volume of dead wood and the snag volume, modifies the pattern of decay stages and also reduces the tree species diversity and the diversity of tree microhabitats. Yet, in the framework of sustainable forest management, a better knowledge of the factor influencing the occurrence of dead wood would allow foresters to adopt scientifically-base practices to preserve biodiversity.…”
Section: Introductionsupporting
confidence: 50%
“…In similar ecological contexts, i.e., French mountain forests with soils of medium to high fertility, local studies have found values comparable to ours: Pernot et al (2013), considering six distinct forest sites in French mountain forests found an average total volume of deadwood of 58 m 3 ha À1 in unmanaged areas. In the mountain beech fir forests of the central Pyrenees, Larrieu et al (2012) got a lower value (around 40 m 3 ha À1 ) but with a much higher counting limit for deadwood components (more than 60 cm in girth). In the beech fir forest in our study area, Grosso (2012) reported an average value of 114 m 3 ha À1 .…”
Section: Evolution Toward Maturity Along the Tsla Gradientmentioning
confidence: 98%
“…In conclusion, the extension of the rotation age increases the amount of woody debris and alters the deadwood profile. Longer periods between harvesting let living trees grow large enough to bear more trunk microhabitats (Larrieu et al, 2011) and to generate woody debris, and encompass more natural disturbance events (strong wind, for example) (Jonsson et al, 2010). The rate of dead wood input is therefore driven by disturbance and tree mortality (Meyer and Schmidt, 2011).…”
Section: Structural Changes In Cws With An Overmature Coppice Componentmentioning
confidence: 99%